Islamic Education Development Prospects: Study of The Future and Its Challenges - Muthmainnah, Sitti; Bachtiar, Fauziah; Yassin, Abdulnassir; Sulistyowati, Endang (Jurnal Pendidikan Progresif, 2025)
Islamic Education Development Prospects: Study of The Future and Its Challenges. Objective: This study aims to analyze the various multidimensional challenges in the development of Islamic Education and offer strategic solutions that are transformative, not merely adaptive. Method: This study used a qualitative approach with a systematic literature review method, by collecting and analyzing literature from reputable journals, scientific books, and relevant reports, both national and international. The literature was selected through strict inclusion and exclusion criteria, covering publications from 2015 to 2024 and relevance to the development of Islamic education. Findings: This study reveals seven main challenges that hinder the development of Islamic Education, namely inconsistency with future needs, negative public perception of graduates, low achievement of eight national education standards, technological disruption and the Society 5.0 era, low digital literacy of educators, a non-contextual curriculum paradigm, and weak character education. These seven challenges are systemically interrelated and demand integrated solutions. The curriculum relevance crisis demands competency-based and integrative reform, the technology gap demands the integration of AI and contextual digital learning, and negative public perception demands performance-based communication strategies and multi-stakeholder collaboration. The innovative solutions offered include the development of a curriculum based on 21st-century values and competencies, the integration of technology and personalized learning, character strengthening based on local wisdom, institutional rebranding through multi-stakeholder collaboration, and partnerships between Islamic educational institutions and the industrial and community sectors. Conclusion: This study confirms that the future development of Islamic education must be rooted in a critical awareness of global dynamics, accompanied by progressive and contextual strategies. These findings provide a conceptual framework that can serve as a foundation for Islamic education reform that not only maintains Islamic identity but also strengthens the readiness of the Muslim generation to respond to future challenges in a visionary and competitive manner. Keywords: islamic education, challenges, solutions, future.